The Izala effect: unintended consequences of Salafi radicalism in Indonesia and Nigeria - Umar, Muhammad Sani (Contemporary Islam, 2020)
Salafism is a revivalist current in Sunni Islam rooted in the teachings of the fourteenth century Hanbalite jurist Taqi ad-Din Ahmad ibn Taymiyyah and the eighteenth century Arabian reformer Muhammad ibn ʿAbd al-Wahhab. Salafis condemn Sufism (Islamic Mysticism) and most forms of popular Muslim piety, including music, as shirk (polytheism) and unbelief. The Wahhabi variant of Salafism is the only form of Islam permissible in Saudi Arabia and the ideology underlying ISIS and other violent extremist movements. This essay shows that despite the expenditure of vast sums by the Saudi and Kuwaiti governments and NGOs efforts to promote Salafi teachings and armed struggles by ISIS and others to impose them, Salafism has a very limited popular appeal. It is based on textual, ethnographic and survey data from two of the most populous Muslim countries, Indonesia and Nigeria. It also shows that efforts to promote Salafism have led to a resurgence of traditional Sufi oriented piety, especially devotional music traditions.